Traceability in the supply chain of specialty coffee small producers through QR technology in Colombia - Paz-Orozco , Helmer; Chong, Mario; Antunes de Souza Lima , Isabela; Anacona-Mopan , Yesid; de Brito Junior , Irineu; Luna, Ana (Revista Brasileira de Engenharia de Biossistemas, 2026)
The global coffee industry faces pressing sustainability challenges, including volatile market prices, low wages, labor shortages, and limited technological adoption, which threaten the viability of small producers, especially in Colombia. In this context, ensuring traceability in the coffee supply chain emerges as a crucial strategy to promote transparency, fairness, and sustainability. This study aims to develop and test a cloud-based traceability system utilizing QR codes in the Colombian specialty coffee supply chain, with a focus on its implementation process and practical implications for small-scale producers. To achieve this, the research adopts a case study methodology, combining direct observations and interviews with nine smallholder coffee producers in Cauca. A cloud-based traceability tool was developed and tested to track the movement of coffee lots along the supply chain, from farmers to consumers. The results demonstrate that the system enhances data entry accuracy, facilitates real-time access to information, and fosters trust among stakeholders. Moreover, it facilitates the documentation of product origin, quality, and sustainability attributes, reducing risks of fraud and improving market access for producers. The study concludes that QR-based traceability is a cost-effective and scalable solution for small-scale producers, contributing to more sustainable and transparent agri-food supply chains.